Analysis on boundary conditions of soft switching for DC electric spring with parallel topology. Issue 12 (20th April 2021) - Wang, Qingsong; Zha, Daojun; Cheng, Ming; Deng, Fujin; Buja, Giuseppe
Abstract: The concept of DC electric spring (DCES) has been introduced some years ago to solve the voltage stabilisation issue caused by the high penetration of intermittent renewable energy sources (RESs) into DC power systems. Recently, a featured DCES topology has been proposed, comprising an isolated three‐port DC/DC converter and an embedded energy storage system. The three ports are connected to a DC power system at the supply side, the critical load (CL) and the non‐critical load (NCL) at the user side, whilst the energy storage system is paralleled at the CL port. To improve the performance of the topology, this paper investigates the chance of making soft the switching of the DCES converters. After the DCES operation is analysed, equations describing the currents transients during switching have been worked out, from which the boundary conditions for zero‐voltage switching (ZVS) to occur are formulated and the resultant ZVS zone is illustrated with the help of visual graphs. The boundary conditions are examined to evaluate how the circuit parameters influence the extension of the ZVS zone. The examination shows that a suitable selection of the parameters widens the ZVS zone notably; its optimal extension is then found for a case study. The effectiveness of the ZVS findings for the featured DCES topology is validated by both simulation and experiment results.